2000
DOI: 10.1098/rspb.2000.1182
|View full text |Cite
|
Sign up to set email alerts
|

Fatal attraction in rats infected withToxoplasma gondii

Abstract: We tested the hypothesis that the parasite Toxoplasma gondii manipulates the behaviour of its intermediate rat host in order to increase its chance of being predated by cats, its feline de¢nitive host, thereby ensuring the completion of its life cycle. Here we report that, although rats have evolved anti-predator avoidance of areas with signs of cat presence, T. gondii's manipulation appears to alter the rat's perception of cat predation risk, in some cases turning their innate aversion into an imprudent attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
487
4
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 677 publications
(513 citation statements)
references
References 32 publications
12
487
4
10
Order By: Relevance
“…If the parasite is currently in a rat, but needs to get into a cat, it makes sense for the parasite to manipulate the behaviour of its rat host to improve its chances of getting into a cat! Discovering that T. gondii makes rodents less afraid of cat odour [4,7] further embedded this idea. It could be argued that such a 'perfect' manipulation could not have come about without the necessary selective pressures, therefore providing support for the idea that Toxoplasma manipulates rodent behaviour to enhance predation by cats.…”
Section: Could Such Appropriate Behavioural Changes Be Coincidental?mentioning
confidence: 99%
See 1 more Smart Citation
“…If the parasite is currently in a rat, but needs to get into a cat, it makes sense for the parasite to manipulate the behaviour of its rat host to improve its chances of getting into a cat! Discovering that T. gondii makes rodents less afraid of cat odour [4,7] further embedded this idea. It could be argued that such a 'perfect' manipulation could not have come about without the necessary selective pressures, therefore providing support for the idea that Toxoplasma manipulates rodent behaviour to enhance predation by cats.…”
Section: Could Such Appropriate Behavioural Changes Be Coincidental?mentioning
confidence: 99%
“…However, it is notoriously easy to interpret behavioural changes to fit your expectations, so any inference based on behavioural changes should be treated with caution. There is no direct evidence (either from predation studies or observed mortality in the wild) that rodents infected with T. gondii actually do get caught by cats more often, although it could be argued that the finding that infected rodents are less afraid of cat odour (specifically urine) [4,7], provides strong indirect evidence. However, we do not agree with this, as a decreased fear of cat urine does not necessarily guarantee enhanced predation by cats.…”
Section: Do Observed Behavioural Changes Actually Translate Into An Imentioning
confidence: 99%
“…Tachyzoites were collected from the peritoneal cavity of infected mice and used to inoculate rats. The rats were intraperitoneally injected with 107 tachyzoites of T. gondii at the Department of Veterinary Pathology, Islamic Azad University, Tabriz Branch-Iran (Berdoy et al, 2000).…”
Section: T Gondii Infectionmentioning
confidence: 99%
“…Desde os anos 60 vem aumentando o interesse por parte de pesquisadores a respeito das mudanças comportamentais apresentadas por animais parasitados (Berdoy et al, 2000;Campbell e Fraser, 1961;Donovick e Burright, 1987;Havlíček et al, 2001;Holmes e Bethel, 1972; Keimer e Read, 1991).…”
Section: Movimentação Espontânea Em Campo Aberto -Machosunclassified
“…Alguns autores afirmam que essas alterações são consequências de danos causados ao sistema nervoso, ou seja, efeito colateral da infecção (Hay et al, 1983;Hrdá et al, 2000). Já outros autores acreditam que esses parasitos são capazes de liberar substâncias que atuam como neurotransmissores que podem influenciar o comportamento do hospedeiro (Berdoy et al, 2000;Biron et al, 2005;Webster, 2007). De qualquer maneira, seja efeito colateral da infecção, seja por produção de neurotransmissores, é muitas vezes visível a alteração no comportamento de animais experimentalmente infectados.…”
Section: Movimentação Espontânea Em Campo Aberto -Machosunclassified